Pertimbangan Hakim Pengadilan Agama dalam Mengabulkan Permohonan Dispensasi Nikah di Bawah Umur - Evi Rohmatzzuhriyah; Kasuwi Saiban; Andi Poerwanto Soedjatmiko; Khotbatul Laila (University of Merdeka Malang, 2022)
The submission of a marriage dispensation application is almost the same as the submission of other civil cases, but if the proposed procedure is not fulfilled or is not appropriate when submitting a marriage dispensation application, the application cannot be accepted/rejected. Basically, the dispensation for underage marriage is a marriage that is carried out to make the prospective bride and groom who have not reached the minimum age of marriage, which is at least 19 years for men and at least 16 years for women in accordance with Law No. 1 of 1974 article 7 paragraph ( 1) . However, the consideration of the Sidoarjo Religious Court Judge in the application for a marriage dispensation was based on the benefit principle, in which the judge saw the two prospective brides and if the request was not granted, it was feared that behavior would further violate existing rules and norms, and so that prospective children who will receive justice will be recognized as legitimate children and have complete parents with marital status recognized by the state Dispensation, Marriage, Minors